Personality Disorders and Psychological Functioning Among Latina Women with Eating Disorders. Issue 3 (3rd July 2017) - Minnick, Alyssa M.; Cachelin, Fary M.; Durvasula, Ramani S.
Abstract: Little is known about personality disorders (PD) and comorbidities among Latinas with eating disorders (ED). The dysregulation and chronicity of PDs can complicate and augment the symptomatology of EDs. This set of analyses provides a preliminary examination of PD and psychopathology in a sample of Latina women with ED. Participants ( N = 34) were administered the Structured Clinical Interview for the Diagnostic and Statistical Manual, Eating Disorders Examination, and Millon Clinical Multiaxial Inventory-III to assess personality pathology, and questionnaires (Beck Depression Inventory-II and Brief Symptom Inventory) to assess psychological functioning. Results indicated the most common clinically significant trait in the sample was depressive personality (50% of the sample had a score of 75 or higher on this trait). For Bulimia Nervosa (BN) and Binge Eating Disorder (BED), avoidant (41%) and depressive (65%) personalities, respectively, were the most common clinically significant traits. Anxiety disorders were the most common psychiatric diagnoses, and 52.9% of the sample reported both clinically significant PD traits and other major psychopathology. There were no significant differences between the BED and BN groups on prevalence of PD traits and psychopathology. This pilot study highlights the need for further examination of PD and psychopathology in Latinas with ED. Unlike previous research with White women, we found no differences on PD and psychopathology between BED and BN, and the most prevalent PDs among Latinas were different than White women. Personality and psychological functioning should be assessed in all patients with ED, with ongoing research focused on identifying patterns in understudied groups such as Latinas, a practice that may improve treatment for this underserved population.